Assembly for semi-correlation analysis of samples using cryogenic scanning electron microscopy and cryogenic Raman micro-spectroscopy - Laznicka, Tomas; Kizovský, Martin; Hrubanová, Kamila; Ježek, Jan; Mrazova, Katerina; Obruča, Stanislav; Samek, Ota; Krzyžánek, Vladislav (MEASUREMENT SCIENCE AND TECHNOLOGY, 2025)
Keywords: BF; MF

The characterization of halophilic polyhydroxyalkanoate-producing bacteria from brine in Solivar near Prešov (Slovakia) - Adhvaryu, Shivani; Kiskova, Jana; Piknova, Maria; Malinicova, Lenka; Beck, Terezia; Buchtikova, Iva; Kourilova, Xenie; Kizovský, Martin; Samek, Ota; Obruča, Stanislav; Pristas, Peter (World Journal of Microbiology and Biotechnology, 2025)
The present study aims to isolate and investigate temporal variability of the halophilic and halotolerant microbiota present in brine from former salt mine Solivar, Prešov (Slovakia) especially with respect to with their ability to produce polyhydroxyalkanoates (PHA). Brine sampling was performed in the year 2020 and 2021 and samples were inoculated on the R2A medium with 5% NaCl for the bacterial isolation. We obtained a total of 53 halophilic isolates and one halotolerant isolate, all of which were tested for their ability to produce PHA via Nile Blue A staining, Raman spectroscopy and Gas chromatography. The low diverse halophilic microbiota was dominated by Proteobacteria members (mainly Halomonas, Halovibrio, and Chromohalobacter sp.) and some of these bacteria represent newly identified taxa. Around 80% of the isolates were able to produce PHA during growth on glucose-rich media, which highlights the importance of PHA for adaptation to high-salinity environments. Poly(3-hydroxybutyrate) (PHB) was the main type of PHA produced with the yield up to 2.76 g/L in Halovibrio sp. HP20-59. Overall, our investigation pointed out that brine from Solivar shows genetically variable community of halophilic bacteria most of which are capable of accumulation of PHA, hereby confirming the high biotechnological potential of halophilic bacteria.
Keywords: BF; MF

What keeps polyhydroxyalkanoates in bacterial cells amorphous? A derivation from stress exposure experiments - P. Sedláček; Slaninová, E.; Enev, V.; Koller, M.; J. Nebesářová; I. Márová; K. Hrubanová; V. Krzyžánek; O. Samek; S. Obruča (Appl. Microbiol. Biotech., 2019)
Keywords: BF; MF

Morphological and Production Changes in Planktonic and Biofilm Cells Monitored Using SEM and Raman Spectroscopy - K. Hrubanová; V. Krzyžánek; O. Samek; R. Skoupý; M Šiler; J Ježek; S. Obruča; P. Zemánek (Microscopy and Microanalysis, 2017)
Keywords: BF; MF

The presence of PHB granules in cytoplasm protects non-halophilic bacterial cells against the harmful impact of hypertonic environments - S. Obruča; P. Sedláček; F. Mravec; V. Krzyžánek; J. Nebesářová; O. Samek; D. Kučera; Pavla Benešová; K. Hrubanová; M. Milerová; I. Márová (New Biotechnol., 2017)
Keywords: BF; MF

Accumulation of PHA granules in Cupriavidus necator as seen by confocal fluorescence microscopy - F. Mravec; S. Obruča; V. Krzyžánek; P. Sedláček; K. Hrubanová; O. Samek; D. Kučera; Pavla Benešová; J. Nebesářová (FEMS Microbiology Letters, 2016)
Keywords: MF

Accumulation of Poly(3-hydroxybutyrate) Helps Bacterial Cells to Survive Freezing - S. Obruča; P. Sedláček; V. Krzyžánek; F. Mravec; K. Hrubanová; O. Samek; D. Kučera; Pavla Benešová; I. Márová (PLoS ONE, 2016)
Keywords: MF

Evaluation of 3-hydroxybutyrate as an enzyme-protective agent against heating and oxidative damage and its potential role in stress response of poly(3-hydroxybutyrate) accumulating cells - S. Obruča; P. Sedláček; F. Mravec; O. Samek; I. Márová (Appl Microbiol Biotechnol, 2016)
Keywords: MF

Quantitative Raman Spectroscopy Analysis of Polyhydroxyalkanoates Produced by Cupriavidus necator H16 - O. Samek; S. Obruča; M Šiler; P. Sedláček; Pavla Benešová; D. Kučera; I. Márová; J Ježek; Silva Bernatová; P. Zemánek (Sensors, 2016)
Keywords: MF

Cryo-SEM and Raman Spectroscopy Study of the Involvement of Polyhydroxyalkanoates in Stress Response of Bacteria - V. Krzyžánek; K. Hrubanová; O. Samek; S. Obruča; I. Márová; Silva Bernatová; M Šiler; P. Zemánek (Microscopy and Microanalysis, 2015)
Keywords: MF